The depression index in the Zulliger Comprehensive System (ZSC) - Villemor-Amaral, Anna Elisa de; Machado, Maria Aparecida dos Santos (Paidéia (Ribeirão Preto), 2011)
The aim of this paper is to verify the validation Zulliger in System-Comprehensive (ZSC) in Brazil, considering the indicators of depression of the DEPI Constellation in the Rorschach-SC. The participants were 54 women, 27 patients with depression and 27 non-patients. The instruments were the SCID-I, questionnaire for the identification and Zulliger test. The time of application of the instruments was 45/100 minutes. The protocols were coded and recoded by another researcher blind and any disagreements were resolved by a third judge. After descriptive statistical analysis, was the t-student test. Among the variables of the DEPI, were substantial FD + V, Sum-SH, Index-egocentric, CF + C < FC, mixed-determinants and Intelectualization Concluding, the ZSC is a tool that can help in the diagnosis of depression.